The effect of trait emotional intelligence on working memory across athletic expertise - Vaughan, R. S.; Hagyard, J. D.; Brimmel, J.; Edwards, E. J. (Journal of Sports Sciences, 2021)
Research attests to the important contributions of emotional, athletic, and cognitive expertise for sport performance. However, little is known regarding the interplay between trait emotional intelligence, athletic expertise, and working memory. The aim of this research was to examine the interplay between working memory (emotional, capacity and ability), trait emotional intelligence and athletic expertise. In total, 437 participants aged between 18 and 27 years with a range of athletic expertise (i.e., non-athlete n = 96, novice n = 92, amateur n = 85, elite n = 83, and super-elite n = 81) completed the Trait Emotional Intelligence Questionnaire Short Form, an Emotion Recognition Task (i.e., working memory-emotional), a Spatial Span Task (i.e., working memory-capacity), and a Spatial Working Memory Test (i.e., working memory-ability). Structural equation modelling indicated a significant positive relationship between trait emotional intelligence and all three components of working memory (i.e., emotional, capacity and ability). Also, this differed over athletic expertise whereby those with more expertise reported larger effects than those with less expertise. These findings suggest that trait emotional intelligence is important for working memory in athletes. Moreover, the link between cognitive and affective processes are increasingly relevant as athletes develop expertise levels.